(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The encyclopedic dictionary which includes scientific, conceptual, and terminological apparatus related to the study of modern Turkic people languages is one of the main measures to preserve the Turkic unity and identity in globalization. The formation of a systematic, competent representation of the Turks about historical and ethnic, cultural, political, linguistic, and geographical features helped to reveal the significance of the formation of historical consciousness. One of the main advantages of the encyclopedic dictionary is the study of Turkological scientific terminology and scientific-conceptual apparatus as its independent metatheme. Such research allows to determine the lexicological corpus in the Turkic languages, to form a systematic methodology of Turkological science, to use the scientific metalanguage, to work with conference materials, and to organize discussions. Specific features of the national mentality that creates a language image of the world can be distinguished in the word-formation system of this source. This wide research is carried out not only within the framework of linguistic science, but also at the intersection of anthropology, sociology, cultural studies, cognitive and geographical sciences. From this perspective, the scale of financing for this research is justified. For realization of the project, diachronous and synchronous, comparative-historical and diachronic-etymological, descriptive and contrastive, statistical, linguistic-mathematical and quantitative, social survey, conceptual analysis, associative and experimental methods of linguistic and geographical sciences. One of the main features of the article is the study of the scientific terminology of Turkology as a separate metalanguage. Key words: Turkology, dictionary, metalanguage, encyclopedic dictionary, term, terminology, ethnos, spiritual and cultural value.